Does industrial policy impact capital flows? - Mehra, Rishita (2024)
This study explores the relationship between industrial policy and capital flows, focusing on how government interventions through industrial policy influence the movement of capital across borders. It examines the impact of industrial policy shocks on gross capital inflows and outflows, alongside other macroeconomic variables like consumer confidence, GDP per capita and investment. The study employs a panel Vector Autoregression (PVAR) methodology, analysing data from 34 primarily high-income countries. The findings suggest that industrial policy shocks cause a drop and then subsequent increase in capital flows after which its effect dissipates. Capital flows are thus highly responsive to business cycle frequencies and changes in investor sentiment. It also finds that industrial policy shocks lead to increases in consumer confidence, but also leads to a fall in investment and GDP per capita levels before the impact of the shock declines. Further, the FEVDs show that apart from previous levels of gross capital inflows and outflows themselves, industrial policy predicts around 60 - 65 percent of their future levels. This research contributes to the literature by shedding light on the relationship between industrial policy and capital flows. The study underscores the need for further investigation into the behaviour of industrial policy and the channels through which it may impact capital flows.